Literary translation : a practical guide - Landers, Clifford E. (Multilingual Matters, 2001)
"In Literary Translation: A Practical Guide, both beginning and experienced translators will find pragmatic techniques for dealing with problems of literary translation, irrespective of the original language. Certain challenges and certain themes recur in translation, whatever the language pair. This guide proposes to help the translator navigate through them. There are guidelines that can help us work our way through, to use a Borgesian metaphor, the seemingly infinite labyrinth of forking paths. That is the purpose of this book."--Jacket
Keywords: Translating and interpreting.; Literature -- History and criticism -- Theory, etc.; Traduction littéraire.; Littérature -- Histoire et critique -- Théorie, etc.; LANGUAGE ARTS & DISCIPLINES -- Translating & Interpreting.; Literature -- Theory, etc.; Translating and interpreting; Literatur; Übersetzung; Linguística.; Tradução (teoria; técnicas); guide book.; handbook.; language pairs.; literary translation.; practical guide.; pragmatics.; translation of fiction.; translation studies.; translation.; Criticism, interpretation, etc.